2021
DOI: 10.3390/fib9020008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Short Fiber Composite Properties by an Artificial Neural Network Trained on an RVE Database

Abstract: In this study, an artificial neural network is designed and trained to predict the elastic properties of short fiber reinforced plastics. The results of finite element simulations of three-dimensional representative volume elements are used as a data basis for the neural network. The fiber volume fraction, fiber length, matrix-phase properties, and fiber orientation are varied so that the neural network can be used within a very wide range of parameters. A comparison of the predictions of the neural network wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Breuer et al applied ANN for short fiber composites under representative volume element database. The elastic properties of short fiber reinforced plastics were evaluated and results showed that ANN predicts the stiffness in good manner 18 . Wang et al used ANN to predict the tensile strength of ultrafine glass fiber felts.…”
Section: Introductionmentioning
confidence: 99%
“…Breuer et al applied ANN for short fiber composites under representative volume element database. The elastic properties of short fiber reinforced plastics were evaluated and results showed that ANN predicts the stiffness in good manner 18 . Wang et al used ANN to predict the tensile strength of ultrafine glass fiber felts.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that ANN model outperformed MLR in the prediction accuracy of elongation at break and breaking strength. Breuer et al used ANN to predict the short fiber composite properties using RVE database [ 22 ]. The prediction of the elastic properties of short fiber reinforced plastics by ANN has been compared with additional finite element results.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an ANN is trained to predict the elastic properties of short fiber reinforced plastics in [52].…”
Section: Data-based Multiscale Modeling and Simulationmentioning
confidence: 99%